C. trachomatis Pgp3 antibody prevalence in young women in England, 1993-2010. - Paddy Horner; Kate Soldan; Sueli M Vieira; Gillian S Wills; Sarah C Woodhall; Richard Pebody; Anthony Nardone; Elaine Stanford; Myra O McClure (PLoS ONE)
Seroepidemiology of chlamydia can offer study opportunities and insights into cumulative risk of exposure that may contribute to monitoring the frequency of, and control of, genital chlamydia-the most commonly diagnosed STI in England. We undertook retrospective anonymous population-based cross-sectional surveys using an indirect IgG ELISA for chlamydia Pgp3 antibody. Sera from 4,732 women aged 17-24 years were tested. Samples were taken at 3-yearly intervals between 1993 and 2002, a period during which other data suggest chlamydia transmission may have been increasing, and from each year between 2007 and 2010. Seroprevalence increased in 17-24 year olds over time between 1993 and 2002. Between 2007 and 2010, age-standardised seroprevalence among 17-24 year olds decreased from 20% (95% CI: 17-23) to 15% (95%CI 12-17) (p = 0.0001). The biggest drop was among 20 to 21 year olds, where seroprevalence decreased from 21% in 2007 to 9% in 2010 (p = 0.002). These seroprevalence data reflect some known features of the epidemiology of chlamydia infection, and show that exposure to antibody-inducing chlamydia infection has declined in recent years. This decline was concurrent with increasing rates of screening for asymptomatic chlamydia. Serology should be explored further as a tool for evaluation of chlamydia control, including chlamydia screening programmes.